PUBLIC SMOKING PROGRAMS OF THE TOBACCO INSTITUTE (Tufts Archival Research Center, 2007)
Outline of Public Smoking Programs of Philip Morris including details on consulting scientists on ETS (environmental tobacco smoke) and indoor air quality, changing the face of the media concerning ETS and indoor air quality, increasing journal integrity about ETS, maintaining scientific integrity, focusing on ventilation as solution to current problem, approaching labor unions as allies, and approaching smokers as allies.